Histopathological Diagnosis of Hysterectomy Specimens in Abnormal Uterine Bleeding - Huma Tahseen, Shabana Khokhar, Naila Atif, Saima Qurban, Hafiza Naveeda Khurshid, Mahliqa Maqsud (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) is a common and distressing condition effecting predominantly perimenopausal women. Heavy menstrual bleeding (HMB) is the most common presentation of AUB. There are many structural and non structural causes of AUB. Histopathology of endometrial curettings is well studies before but the histopathological patterns of hysterectomy specimens are not well studied. Objective: The objective of this study is to: Find out histopathological diagnosis of hysterectomy specimens in patients of AUB. Study Design: Retrospective Cohort study. Place and Duration of Study: Gynecology and Pathology departments of Azra Naheed and Rashid Latif medical colleges from January 2022 to January 2023. Methods: Histopathology reports of all hysterectomies done for AUB in both medical colleges allied hospitals were retrieved retrospectively and evaluated in detail. Four age groups were defined 30-40 years, 41-50, 51-60 and 61-70 years. Various patterns were recorded overall and separately for each group and results established. Results: A total of 221 abdominal hysterectomy histopathology reports were retrieved and evaluated. All hysterectomies were performed for AUB during one year period between January 2022 to January 2023. 40(18.09%) women were between 30-40 years of age, 134(60.6%) were between 41-50 years of age, 39(17.6%) were between 51-60 years of age and 08(3.61%) patients were between 61-70 years of age. Distorted proliferative phase endometrium was seen in 28(12.6%) of cases, Adenomyosis was seen in 76(34.38%), endometrial polyps in 19(8.55%), fibroids in 92(41.6%), metaplasia 07(3.1%), hyperplasia 10(4.5%), and endometrial carcinoma was seen 09 (4.07%) of cases. Conclusion: AUB is most common in perimenopausal women. Fibroids, Adenomyosis, and disordered proliferative endometrium were most common in perimenopausal women while carcinoma endometrium was most common cause of AUB in postmenopausal women. This study will help Gynecologists to better find out the cause of AUB and treat accordingly. Keywords: Abnormal uterine bleeding (AUB), Heavy menstrual bleeding (HMB), Perimenopausal, Hysterectomy. Histopathology, Endometrium